2021
DOI: 10.1101/2021.03.06.21252603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BNT162b2 COVID-19 mRNA vaccine elicits a rapid and synchronized antibody response in blood and milk of breastfeeding women

Abstract: We describe the dynamics of the vaccine-specific antibody response in the breastmilk and serum in a prospective cohort of ten lactating women who received two doses of the Pfizer-BioNTech BNT162b2 COVID-19 mRNA vaccine. The antibody response was rapid and highly synchronized between breastmilk and serum, reaching stabilization 14 days after the second dose. The predominant serum antibody was IgG. The response in the breastmilk included both IgG and IgA with neutralizing capacity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
1
30
0
3
Order By: Relevance
“…Other groups have also found SARS-CoV-2 spike and RBD-specific IgG [11][12][13][14] in human milk after vaccination in addition to IgA. Here, we showed that SARS-CoV-2 spike and RBD-specific IgG are found at significantly higher levels in T4 compared to T1.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Other groups have also found SARS-CoV-2 spike and RBD-specific IgG [11][12][13][14] in human milk after vaccination in addition to IgA. Here, we showed that SARS-CoV-2 spike and RBD-specific IgG are found at significantly higher levels in T4 compared to T1.…”
Section: Discussionsupporting
confidence: 58%
“…This is similar to the kinetics found in Baird et al and Friedman et al, and could either be a function of time after the initial antigenic stimulation of dose one, or an immunological need for dose two. 11,12 As the humoral immunological response in lactating individuals has been recently shown 18 to be more dependent on the booster dose of vaccination compared to non-lactating individuals, the latter is highly probable. Thus, whether significant amounts of antigen-specific antibodies can be elicited after administering one-dose regime vaccines, requires confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that milk produced by infected mothers is a source of anti-SARS-CoV-2 antibodies 6 , and two reports have demonstrated the existence of anti-SARS-CoV-2 antibodies in women vaccinated with Moderna® and Pfizer-BioNTech® mRNA vaccines 7,8 . If this exerts a protective effect for breastfed infants remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, COVID-19 appears to be less prevalent and, generally, less severe in infants (8,9), and there is evidence that breastmilk from mothers with a history of COVID-19 infection contains speci c IgA with an activity against SARS-CoV-2 (9-13). Furthermore, prospective cohort studies have found that anti-SARS-CoV-2 IgA and IgG generated by anti-COVID-19 mRNAbased vaccines administered to lactating and pregnant mothers are transferred to their babies via breastmilk (14,15) and umbilical cord blood (16, 17), while COVID-19 mRNA does not (18,19). Moreover, evidence suggests that vaccine-induced immune responses are even greater than natural infection-induced immunity (17), due to an IgG-dominant response (20).…”
Section: Introductionmentioning
confidence: 99%